Who Drives Audit Quality in Indonesia? A Study of Board Attributes and Firm Characteristics - Utami, Ayu Prasakti; Meilani, Sayekti Endah Retno; Mustikawati, Susilaningdyah (Universitas Sultan Ageng Tirtayasa, 2025)
This study investigates the influence of board and firm-specific characteristics on audit quality in Indonesia. Board characteristics include board size, number of board meetings, board ownership, board experience, and board gender diversity. Firm-specific characteristics cover firm size, profitability, and leverage. A purposive sampling method was used to select 553 non-financial companies listed on the Indonesia Stock Exchange (IDX) in 2021, and data were analyzed using logistic regression with SPSS 23. The results show that board size and board experience significantly enhance audit quality, while the number of board meetings, board ownership, and gender diversity have no significant effect. Firm size and profitability positively influence audit quality, whereas leverage does not. These findings highlight the importance of specific board and firm attributes in shaping audit outcomes. This research contributes to understanding the role of corporate governance in improving audit quality. It offers practical implications for companies in selecting high-quality auditors and enhancing their governance practices. Future research is encouraged to explore additional variables and broader samples to strengthen insights into audit quality determinants in Indonesia.